An analysis of adherence to the World Health Organisation guidelines pertaining to drug promotional literature by pharmaceutical firms - Malik, Salma; Anantharamu, Tejus; Salmani, M. Fadil; Pradhan, Sapna; Mathur, A. G. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Pharmaceutical companies used Drug Promotion Literatures (DPLs) as a major tool to advertise their new products. World Health Organization (WHO) has set some guidelines for promotion of drug literature. Thus, this study aimed to evaluate various DPLs for their accuracy and credibility as per WHO ethical criteria. Methods: This was an observational and cross-sectional study. Total 100 drugs advertisements published in various medical journals were collected from the library of the college. Advertisements were selected based on inclusion and exclusion criteria. The selected advertisements were evaluated based on the WHO ethical criteria for drug promotion. Results: From 100 advertisements, 73 were single drug whereas 27 were fixed drug combinations. Antimicrobials (16%) were the most promoted advertisements. Only 28% of the advertisements carried references to support their claim. Out of which majority (91.78%) were from journal articles. The generic name, brand name, names of active ingredients, manufacturer, distributor and dosage regimen were mentioned in majority of advertisements. Drug interactions (12%), contraindications (22%), precautions (24%) and side effects (22%) were least mentioned in the advertisements. Conclusions: It was observed that none of the advertisement followed all the guidelines laid down by WHO. Pharmaceutical companies should follow ethical regulatory measures to promote their product in various journals. The regulatory authority must ensure the pharmaceutical companies to follow ethical guidelines for publishing various drug promotional literatures.